The effect of Pd on electrical properties of Sn02 in CH4 detection - Dennis, John Ojur (2001)
The effect of Pd on electrical properties of Tin (IV) oxide (SnO2) as an element for CH4 detection is investigated for samples prepared from a mixture of powders of (100-x)Sn02.xPd (0 =< x wt % =< 15) which were pressed into pellets and sintered at various temperatures ranging from 600°C to 1100°C. In order to achieve the objectives of the study, a Gas Sensor Characterization System (GSCS) was built. The main component of the GSCS is an airtight gas sensor test chamber with a volume of about 405 cm3. The conductance of a sample is monitored in this chamber at various operating temperatures, flow rate of carrier gas (synthetic air) and applied voltages when the sample was exposed to small concentrations (in ppm) of CH4 in air. The GSCS is interfaced, via an ADC card, with a computer for data acquisition, storage and analysis. Results show that SnO2 without Pd cannot detect CH4 in air up to an operating temperature of 400°C. However, the modification of Sn02 by the addition of Pd significantly enhances its sensitivity to CH4 with the highest sensitivity occurring at around 400°C. The general trend is a sharp increase in sensitivity of SnO2 up to about 3wt% Pd and thereafter a gentle decrease up to 15 wt% Pd. Fifty percent (50 %) response time of about 20 seconds and recovery time of 7.27 minutes were calculated for samples with 3 wt% Pd sintered at 900°C. The relationship between sensitivity and the concentration of CH4 in air at the operating temperature of 400°C can be approximated by the logarithmic function. Results on the effect of sintering temperature show that the sensitivity of Sn02 with Pd as additive is higher for samples sintered at lower temperatures. The flow rate of the carrier gas was found to significantly affect the sensitivity of samples sintered at lower temperatures. The response and recovery times generally decreased with increasing flow rate of the camer gas. This effect is attributed to increase in the oxygen partial pressure of the carrier gas in the test chamber with increasing flow rate. On the other hand, it was observed that the sensitivity depends on the applied voltage especially for samples sintered at lower temperatures. Measurements on ethane (C2H6) and hydrogen sulfide WS) in air were carried out in order to test the selectivity of some samples to other gases. It was found that sensitivity to C2H6 is higher than sensitivity to CH4 but in the same operating temperature range with a selectivity of about 1.69 at 400°C. H2S was detectable in air with the highest sensitivity at 100°C and decreased to a minimum at 200°C. SEM micrographs of the samples indicate that the Sn02 crystallites are of sub-micron sizes. The Pd concentration in Sn02 determined by AAS was shown to increase with increasing nominal composition of Pd added to Sn02. It was possible to detect Pd in samples with 15 wt% Pd using EDAX but not for samples with nominal composition of =< 10 wt% Pd.